Screening of the Antimicrobial Activity against Drug Resistant Bacteria of Photorhabdus and Xenorhabdus Associated with Entomopathogenic Nematodes from Mae Wong National Park, Thailand - Muangpat, Paramaporn; Yooyangket, Temsiri; Fukruksa, Chamaiporn; Suwannaroj, Manawat; Yimthin, Thatcha; Sitthisak, Sutthirat; Chantratita, Narisara; Vitta, Apichat; Tobias, Nicholas J.; Bode, Helge B.; Thanwisai, Aunchalee (Frontiers in Microbiology, 2017)
Photorhabdus and Xenorhabdus are symbiotic with entomopathogenic nematodes (EPNs) of the genera Heterorhabditis and Steinernema, respectively. These bacteria produce several secondary metabolites including antimicrobial compounds. The objectives of this study were to isolate and identify EPNs and their symbiotic bacteria from Mae Wong National Park, Thailand and to evaluate the antibacterial activities of symbiont extracts against drug resistant bacteria. A total of 550 soil samples from 110 sites were collected between August 2014 and July 2015. A total of EPN isolates were obtained through baiting and White trap methods, which yielded 21 Heterorhabditis and 3 Steinernema isolates. Based on molecular identification and phylogenetic analysis, the most common species found in the present study was P. luminescens subsp. akhurstii associated with H. indica. Notably, 2 species of EPNs, H. zealandica and S. kushidai, and 2 species of symbiotic bacteria, X. japonica and P. temperata subsp. temperata represented new recorded organisms in Thailand. Furthermore, the association between P. temperata subsp. temperata and H. zealandica has not previously been reported worldwide. Disc diffusion, minimal inhibitory concentration, and minimal bactericidal concentration analyses demonstrated that the crude compound extracted by ethyl acetate from P. temperata subsp. temperata could inhibit the growth of up to 10 strains of drug resistant bacteria. Based on HPLC-MS analysis, compound classes in bacterial extracts were identified as GameXPeptide, xenoamicin, xenocoumacin, mevalagmapeptide phurealipids derivatives, and isopropylstilbene. Together, the results of this study provide evidence for the diversity of EPNs and their symbiotic bacteria in Mae Wong National Park, Thailand and demonstrate their novel associations. These findings also provide an important foundation for further research regarding the antimicrobial activity of Photorhabdus bacteria.